In-depth study of lightweight block ciphers: Performance assessment and implementation on sensor motes - Amal Hkiri; Mouna Karmani; Fawaz Hasan Alasmary; Omar Ben Bahri; Ahmed Mohammed Murayr; Mohsen Machhout (Alexandria Engineering Journal)
In the rapidly evolving landscape of the Internet of Things (IoT) and Wireless Sensor Networks (WSN), the need for secure and efficient data transmission is paramount. Block ciphers, which are fundamental cryptographic algorithms used for encrypting data, play a critical role in ensuring data security within these environments. This study delves into the implementation and performance evaluation of lightweight block ciphers, including PRESENT, Piccolo, RECTANGLE, SPARX, and LED, on various sensor motes. The research scrutinizes these cryptographic solutions within the resource-constrained environments characteristic of IoT and WSN deployments. Our investigation commences with a meticulous selection of sensor motes and platforms, enabling realistic simulations and practical evaluations. The Contiki Cooja framework, a comprehensive operating system (OS), development toolkit, and network simulator, was utilized to facilitate these assessments. Subsequently, we conduct a comprehensive performance assessment, rigorously analyzing each cipher's impact on memory usage, power consumption, and execution time. The results reveal that the SPARX cipher emerged as the most resource-efficient, with the lowest memory footprint, while the RECTANGLE cipher required more memory across platforms.